Validity of Risk Assessment Instruments Among Juveniles Who Sexually Offended: Victim Age Matters. (June 2021) - Krause, Chiara; Roth, Alexander; Landolt, Markus A.; Bessler, Cornelia; Aebi, Marcel
Research has identified meaningful subtypes among the heterogeneous population of juveniles who sexually offended (JSO). However, studies that test the validity of risk assessment tools with JSO subtypes are limited. This study compared JSO who offended against a child victim (JSO-C) and JSO who offended against an adolescent/adult victim (JSO-A) with regard to rates of recidivism and the predictive validity of two risk assessment tools (Estimate of Risk of Adolescent Sexual Offense Recidivism [ERASOR] and Juvenile Sexual Offender Assessment Protocol-II [J-SOAP-II]). Data were analyzed from case files of 185 JSO-C and 297 JSO-A aged 12 to 18 years ( M = 14.11, SD = 1.44) from a consecutive sample of JSO with contact sexual offenses. A total of 34 (7.1%) juveniles reoffended sexually, with no significant difference between the subtypes. The present results suggest that the ERASOR, particularly the structured professional judgment, and to a lesser degree the J-SOAP-II are better suited to predicting sexual recidivism in JSO-A than in JSO-C.